Exploring links between socio-ecological systems and psychological distress: a case study in rural Uganda - Thomas Pienkowski; Aidan Keane; Eugene Kinyanda; Birthe Loa Knizek; Caroline Asiimwe; Geoffrey Muhanguzi; E.J. Milner-Gulland (Oryx)
Poor mental health is a leading contributor to the global burden of disease but there is poor understanding of how it is influenced by people's interactions with ecological systems. In a theory-generating case study we asked how interactions with ecosystems were perceived to influence stressors associated with psychological distress in a rural setting in Uganda. We conducted and thematically analysed 45 semi-structured interviews with residents of Nyabyeya Parish. Poverty and food insecurity were the primary reported causes of ‘thinking too much’ and related idioms suggesting psychological distress. Households bordering a conservation area reported that crop losses from wildlife contributed to food insecurity. However, forest resources represented important safety nets for those facing poverty and food insecurity. Commercial agricultural expansion also emerged as a salient theme in the lives of residents, reportedly exacerbating poverty and food insecurity amongst poorer households but contributing incomes to wealthier ones. Our exploratory study suggests how two globally prevalent land uses, nature conservation and commercial agriculture, may influence social determinants of psychological distress in the study area. We highlight co-benefits and trade-offs between global sustainability goals that could be managed to improve mental health.